2022
DOI: 10.1051/0004-6361/202141092
|View full text |Cite
|
Sign up to set email alerts
|

The eROSITA Final Equatorial-Depth Survey (eFEDS)

Abstract: Theoretical models of the co-evolution of galaxies and active galactic nuclei (AGNs) ascribe an important role in the feedback process to a short, luminous, obscured, and dust-enshrouded phase during which the accretion rate of the supermassive black hole is expected to be at its maximum and the associated AGN-driven winds are also predicted to be maximally developed. To test this scenario, we have isolated a textbook candidate from the eROSITA Final Equatorial-Depth Survey (eFEDS) obtained within the performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 111 publications
1
5
0
Order By: Relevance
“…The X-ray spectral analysis provides N H , which is an indicator of obscuring gas properties around AGN. eROSITA already discovered statistically large number of obscured (N H > 10 22 cm −2 ) AGN at z > 0.5 in the eFEDS field (Brusa et al 2022;Toba et al 2022). As already discussed in Liu et al (2022), we note that the uncertainty of N H is not small, reaching ∆ log(N H /cm −2 ) = 0.67 for the sample (see top right panel of Fig.…”
Section: Obscuration Propertiessupporting
confidence: 74%
See 1 more Smart Citation
“…The X-ray spectral analysis provides N H , which is an indicator of obscuring gas properties around AGN. eROSITA already discovered statistically large number of obscured (N H > 10 22 cm −2 ) AGN at z > 0.5 in the eFEDS field (Brusa et al 2022;Toba et al 2022). As already discussed in Liu et al (2022), we note that the uncertainty of N H is not small, reaching ∆ log(N H /cm −2 ) = 0.67 for the sample (see top right panel of Fig.…”
Section: Obscuration Propertiessupporting
confidence: 74%
“…As shown in the figure, there is one spec-z source in the region of the extremely red quasar color. The source is ERO_ID = 608, which Brusa et al (2022) already identified as an X-ray luminous obscured AGN with strong [OIII]λ5007 outflow feature, undergoing strong AGN feedback. This is consistent with one of the notable features of extremely red quasars (Zakamska et al 2016).…”
Section: Obscuration Propertiesmentioning
confidence: 99%
“…This criterion includes sources with either spectroscopic redshift (CTP_REDSHIFT_GRADE = 5) or the photoz estimates of the two methods agree (CTP_REDSHIFT_GRADE = 4) or agree within a tolerance level (CTP_REDSHIFT_GRADE = 3; for more details see Sect. 6.3 of Salvato et al 2022). Liu et al (2022) performed a systematic X-ray spectral fitting analysis on all the X-ray systems.…”
Section: X-ray Sources In the Efeds Fieldmentioning
confidence: 99%
“…The eFEDS X-ray catalogue includes 27910 X-ray sources detected in the 0.2−2.3 keV energy band with detection likelihoods ≥ 6, that corresponds to a flux limit of ≈ 7 × 10 −15 erg cm −2 s −1 in the 0.5 − 2.0 keV energy range (Brunner et al 2022). Salvato et al (2022) presented the multiwavelength counterparts and redshifts of the X-ray sources, by identifying their optical counterparts. Two independent methods were utilized to find the counterparts of the X-ray sources, NWAY (Salvato et al 2018) and ASTROMATCH (Ruiz et al 2018).…”
Section: X-ray Sources In the Efeds Fieldmentioning
confidence: 99%
“…) and stars (Schneider et al 2022); the X-ray variability properties of the detected sources (Boller et al 2022;Buchner et al 2022); the X-ray spectral analysis of the point sources (Liu et al 2022b); the X-ray morphological analysis of the clusters (Ghirardini et al 2022); the optical and lensing analysis of the X-ray clusters (Ramos-Ceja et al 2022;Chiu et al 2022;Bahar et al 2022, Ota et al, in prep. ); the properties of non-active galaxies detected by eROSITA (Vulic et al 2022), and the discovery of some extreme AGN (Toba et al 2022;Brusa et al 2022). Earlier works based on the eFEDS data have been published and include the discovery of a supercluster (Ghirardini et al 2021) and a very high-redshift quasar (Wolf et al 2021).…”
Section: Introductionmentioning
confidence: 99%